Responsibilities of PPATs who are Late in Registering Deeds Has Been Made to the Office of the National Land Agency - Arty Retno Sari; Setyawati Setyawati (Sultan Agung Notary Law Review, 2022)
PPAT services as an authorized position are very useful for certain people, especially for people who do not understand the law. Some people who do not understand the law feel unable to handle the legal problems they face, given the limited data around the law. For quick access to PPAT-related matters, the national office must issue a receipt for submitting a registration application, for example, a deed from the PPAT and submit the file to the appropriate PPAT. This responsibility not only affects the progress of understanding or compliance with the law, but also considers the greater legal impact on PPAT's thoughts or behavior, both positive and negative. Because of the importance of evidence as a way of affirmation that can provide legal certainty and guarantee to the right holder, the making of a deed of transfer of land rights as a reason to follow land registration data through the sale and purchase of land rights must be in accordance with the timeframe previously specified in Article 40 paragraph (1) Government Regulation Number 24 of 1997 concerning Land Registration.